HADIS-HADIS EKOLOGI DALAM KONTEKS PERINDUSTRIAN DI INDONESIA - Chandra, Agus Firdaus (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2016)
As the religion of rahmatan lil ‘alamin, Islam does not only concern with how mankinds worship to Allah (ibadah), and establish relationship among mankinds (muamalah) but also protect and preserve ecological systems around them as main purposes of Islamic laws (maqashid al-syari’ah). As the best role model (uswah al-hasanah), Prophet Muhammad pbuh has shown especially how to deal with ecology in relation to industrial activities. As a predominantly Moslem country, hadeeth as a religious text is expected to a great influence on the way of life including industrial world in order to realize public welfare and prosperity by industrial practitioners in Indonesia in general. However, religious passion has not had a positive impact in industrial world. Welfare as the main goal can only be enjoyed by a small group of people. Dealing with the phenomena, this article, therefore, aims at discussing hadeeths in relation to ecology and presenting analysis the implementation of the hadeeths in industrial practices in Indonesia